Investigation on crystal structure, magnetic and near-infrared absorption properties of a novel heteroleptic nickel-bis-1, 2-dithiolene compound. (16th August 2017) - Chen, Xuan-Rong; Xue, Chen; Liu, Shao-Xian; Cai, Bin; Wang, Jun; Tao, Jian-Qing; Xue, Yun-Shan; Huang, Xing-Cai; Ren, Xiao-Ming; Liu, Jian-Lan
Graphical abstract: A new heteroleptic nickel-bis-1, 2-dithiolene ion-pair complex was synthesized and characterized structurally. Magnetic susceptibility and UV–Vis-NIR spectral measurements show that the magnetic behavior follows the S = 1 /2 Heisenberg alternating linear-chain model in high temperature range and Curie-Weiss law in low temperature range for1, and a intense near-IR absorption for1 and [BzQl][Ni(dmit)(mnt)]. Abstract: A new heteroleptic nickel-bis-1, 2-dithiolene ion-pair complex, (4-ClBz-1-APy)[Ni(dmit)(mnt)] (1 ) (where 4-ClBz-1-APy + = p-chloro-benzyliden-1-aminopyridinium; dmit 2− = 2-thioxo-1, 3-dithiole-4, 5-dithiolate; mnt 2− = maleonitriledithiolate) was synthesized and characterized structurally. The IR spectra, thermal analysis, magnetic and near-IR absorption properties have been investigated for1 . Complex1 crystallized in monoclinic system with space group P 21 . The anions and cations form the mixed stacked columns separated by the cation columns. The anion stacks are irregular, in which two neighboring heteroleptic [Ni(dmit)(mnt)] − anions are separated by one 4-ClBz-1-APy + cation. The neighboring anions are connected via lateral-to-lateral S…S contacts of dmit 2− ligands and short H…N, H…S and C…S contacts are observed between the cations and the anions. Magnetic susceptibility measurement shows that the magnetic data follows the S = 1 /2 Heisenberg alternating linear-chain model in the temperature range 40–300 K and Curie-Weiss law below 40 K for1 . Salts1 exhibits a intense near-IR absorption in the region of 900–1400 nm, and this near-IR absorption feature makes it to be a promising optical material.